Perspectives on Adapting the Performance Management of Secondary Education Institutions in Romania to European Models - Enache, Mioara (Didactica Danubiensis, 2022)
The fundamental purpose of the secondary education system is to provide, at a higher quality level, solutions to social and individual needs such as: training and development of basic skills, indispensable for the evolution of society, training and development of values ​​and attitudes necessary to educate active and involved citizens, pre-professionalization and professionalization for the socio-professional insertion of young people.